Analisis Faktor Penyebab Ketidaklengkapan Resume Medis Rawat Inap di Puskesmas Cermee Bondowoso - Siti Alifa Lufianti; Rossalina Adi Wijayanti; Demiawan Rachmatta Putro Mudiono; Indah Muflihatin (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
The patient's medical resume form is a summary of the entire period of patient care and treatment as has been attempted by health workers and related parties. Based on a preliminary study in March 2021, researchers obtained data information on incomplete medical resume forms, the highest incompleteness was found in the identification component, which was 86.7%, the next incompleteness was in the Authentication component, which was 80%, the next incompleteness was in the Authentication component. important reports that is equal to 56.7%. The purpose of this study was to analyze the factors causing the incomplete filling of the patient's medical resume form. This type of research uses qualitative research, the subject of this research consists of 1 head of puskesmas, 3 inpatient doctors, and 1 medical record officer, the object of this research is to use an inpatient medical resume form to determine the factors that cause incomplete medical resume forms. inpatient. The results found in this study are that the first priority is that there is no SOP (Standard Operational Procedure) regarding filling out medical resumes, so it is determined efforts to make SOPs for filling out medical resumes in accordance with medical record service standards